PEREMPUAN SEBAGAI OBYEK SEKS DALAM LELUCON DI MEDIA MASSA - Scotia, Annisa (JURNAL ILMU SOSIAL, 2006)
The messages in context of woman representation in anecdote rubric on MATRA magazine had sexism acts. Presenting jokes about woman as sex object with all their inferiority shows it. The language choice, word and sentence structure were not considered with woman sensitivity. Jokes on women representing built stereotype of woman status as subordinate party. The result of study showed that the anecdote rubric in MATRA magazine represented patriarchy ideology because it contained woman bias that still trapped in social stereo-type. The character different between men and woman represents this bias, where that differentiation had became the foundation of sexual job distribution. Man placed in public area (as head of household) and woman placed in domestic area (as housewife). Using word like prostitute, women had been seen as an unmoral human being and prostitution was not a good job for 'nice' women. The word soldier had been also identified to men, so women have considered unable to involve in there. Base on the result of study, researcher had been concluded that this point of view clearly has not been given bargaining and developing position for women. MATRA magazine tend to become a power for dominant group (men) continuing patriarchy ideology and not to become an alternative power for women to escape from patriarchy ideology domination.